NeuroD1 promotes neuroblastoma cell growth by inducing the expression of ALK. Issue 4 (12th March 2015) - Lu, Fangjin; Kishida, Satoshi; Mu, Ping; Huang, Peng; Cao, Dongliang; Tsubota, Shoma; Kadomatsu, Kenji
Abstract : Neuroblastoma is derived from the sympathetic neuronal lineage of neural crest cells, and is the most frequently observed of the extracranial pediatric solid tumors. The neuronal differentiation factor, NeuroD1, has previously been shown to promote cell motility in neuroblastoma by suppressing the expression of Slit2. Here we report that NeuroD1 is also involved in the proliferation of neuroblastoma cells, including human cell lines and primary tumorspheres cultured from the tumor tissues of model mice. Interestingly, the growth inhibition of neuroblastoma cells induced by knockdown of NeuroD1 was accompanied by a reduction of ALK expression. ALK is known to be one of the important predisposition genes for neuroblastoma. The phenotype resulting from knockdown of NeuroD1 was suppressed by forced expression of ALK and, therefore, NeuroD1 appears to act mainly through ALK to promote the proliferation of neuroblastoma cells. Furthermore, we showed that NeuroD1 directly bound to the promoter region of ALK gene. In addition, the particular E‐box in the promoter was responsible for NeuroD1‐mediated ALK expression. These results indicate that ALK should be a direct target gene of NeuroD1. Finally, the expressions of NeuroD1 and ALK in the early tumor lesions of neuroblastoma model mice coincided in vivo . We conclude that the novel mechanism would regulate the expression of ALK in neuroblastoma and that NeuroD1 should be significantly involved in neuroblastoma tumorigenesis. Abstract : In previous report, we showed that NeuroD1 regulated migration of neuroblastoma cells. Here, we found another function that NeuroD1 also promotes the proliferation of both human neuroblastoma cell lines and tumor‐initiating cells from model mice by inducing ALK expression.